Efeito do déficit hídrico em duas variedades de trigo (Triticum aestivum L.) em associação com bactérias promotoras do crescimento vegetal - Furlan, Fernando (2013)
The wheat crop and bacteria Azospirillum brasilense and Herbaspirillum seropedicae has been the subject of research. However, it requires more research involving wheat under the condition of association with these bacteria and conjugated to water deficit in relation to physiological parameters and productive. The objectives of this study was to evaluate the association of Herbaspirillum seropediceae SMR1 and Azospirillum brasilense Ab-V5, inoculated in two wheat cultivars (CD 120 and Frontana) and whether this association is effective to confer tolerance to Decit water. Eight conditions combining the inoculation (s) bacterium (s) and Hs Az with and without addition of nitrogen (N) have been proposed. The experimental design was a randomized block design in a factorial 2 x 8 x 3. The results were subjected to analysis of variance - ANOVA and means were compared by Tukey test at 5% probability GENES program. Deficits were applied at flowering and samples were collected at the beginning of the heading stage, growth stage Zadock 45. Samples were collected at 0 days, 8 days for severe deficit condition and 16 days for partial deficit. Were quantified using the Relative Water Content (TRA), Membrane Stability Index (AEI), total nitrogen (TN) in the leaves, root anatomy and productive parameters (fresh and dry biomass, tiller number, ear number / plant , grain yield / plant and weight of 1000 grains). The partial deficit condition was not perceived in different conditions of inoculation and / or fertilization applied, demonstrating that these cultivars are partially adapted to a water restriction progressive. Conditions containing bacteria (Hs) and (Az and Hs), (Az and N) had TRA similar to plants irrigated control, showing that managed to maintain cell turgor by presenting IEM high (90%). Molecular analysis could confirm the presence of bacteria in inoculated plants, but no differences were observed in root anatomy induced by the presence of bacteria. Plants of cv CD 120 generally showed higher levels of NT in the leaves when subjected to severe deficit and cv Frontana there was a decrease in these levels. In relation to production parameters, plants inoculated with 120 hp CD H. seropedicae showed 52% increase in their fresh biomass compared to the control irrigated, but in severe deficit this increase was 3%. The presence of A. brasilense promoted a 31% reduction in fresh weight compared to the control, but in severe deficit in an improvement of 11% in fresh weight. The association between H. seropedicae, A. brasilense and nitrogen provided a 2% increase in biomass (irrigated) and 101% severe deficit. For hp Frontana values were 0.6%, -12%, -21%, 28%, -18% and -8% in the same conditions. The same trends were observed for dry matter. Regarding NT contents of the leaves, it is noted that the CD 120 hp showed increased levels in the presence of a fluid restriction and cv Frontana, these values had decreased in all conditions. The variable number of tillers did not differ between conditions, cultivate or water condition applied. Plants inoculated with 120 hp CD H. seropedicae had 46% more spikes / plant compared to the control irrigated, and 40% in severe deficit. In cv Frontana no differences were observed. Comparing the data obtained for grain yield per plant between conditions applied (severe deficit irrigated x), the values were proportionally lower in deficit condition, due to less dry, but the plants were capable of maintaining mass values 1000 irrigated grain similar to control in both cultivars